Penguasaan Tanah Oleh Orang Asing Dalam Perspektif Hak Bangsa - Nur, Arif Rachman (Jurnal Mulawarman Law Review, 2018)
The Indonesians has a close relation with land, water, space and natural resources in the territory, in order of the Nations Right to the highest order in the hierarchy of land tenure. But concurrently with the times, not only the Indonesian needed land and buildings, but also foreigners who working in Indonesia. It is the background of enactment of Government Regulation No. 41 of 1996 replaced by Government Regulation No. 103 of 2015 about Residential Ownership by Foreigner. Nevertheless the Government Regulation is considered not nationalists because mortgaging the Indonesia's territory to foreigner for investment reason. The method used in this research is a normative research with statute approach, historical approach and comparative approach. This research used primary legal sources and secondary legal sources incorporating nonlegal resources collected with literature research. Then the legal sources are qualitatively analyzed and then presented descriptively. The results of the study shows: 1) Housing ownership does not necessarily have an implication on land ownership, because the adoption of the Horizontal Separation Principle does not allow foreigners to own land even though they already have buildings on it. However, the period of Right to Use which is too long to reach 80 years can conflict with the Rights of the Nation; 2) Land tenure restriction by foreigners permanent residence in Indonesia is an obligation for the government to respect and protect the Rights of the Nation. The land tenure restriction is carried out by limiting housing ownership in the elaboration of subjects, quota restrictions, zoning, arrangements related to buying and selling and the establishment of duties to supervise the ownership of residential houses for foreigners domiciled in Indonesia.